(untitled) (Al-Qamar, 2021)
Sustainable development and the strategies to its formulation and development in the light of the Prophet’s biography is a very important topic in the light of the current needs of Pakistan and the world. Sustainable development means making progress in the social, political, economic and moral fields. Sustainable development does not depend on economic growth alone. At present, the superiority of a country in the field of science and technology is of paramount importance. There are internal and external factors and challenges in the path of sustainable development. Obstacles to development include dictatorship, luxury of rulers, lack of unity, nationalism, sectarianism, violation of the rights of the weaker sections, nepotism, lawlessness, terrorism, extremism, double standards of the West. Are the main causes. Pakistan’s biggest problem right now is economics. Poverty, unemployment and inflation have affected not only the people but also the country’s development wheel. Therefore, in these circumstances, in order to achieve the goals of sustainable development in the country, it is necessary to set rules and regulations in the light of Sira-e-Taiba so that internal and external difficulties can be tackled.